Disengagement from tasks as a function of cognitive load and depressive symptom severity. Issue 1 (2nd January 2017) - Bowie, Christopher R.; Milanovic, Melissa; Tran, Tanya; Cassidy, Sarah
ABSTRACT: Introduction: Depression is associated with impairment in cognition and everyday functioning. Mechanisms of cognitive dysfunction in depression and the factors that influence strategic deployment of cognitive abilities in complex environments remain elusive. In this study we investigated whether depression symptom severity is associated with disengagement from a working memory task (Paced Auditory Serial Addition Task; PASAT) with parametric adjustment of task difficulty. Methods: 235 participants completed the Beck Depression Inventory, low and high cognitive load conditions of the PASAT, and quality of life. Cognitive disengagement was the sum of consecutive items in which participants did not proffer a response to the trial. Results: Individuals with higher depression severity showed more cognitive disengagement on the high but not low cognitive load trial of the PASAT; they did not differ in number of correct responses. Increased disengagement from the low to high cognitive load was associated with more impaired quality of life. Conclusions: Depression severity is associated with increased disengagement from tasks as difficulty increases. These findings suggest the importance of measuring how cognitive skills are avoided in complex environments in addition to considering performance accuracy. Individuals with depressive symptoms might preferentially avoid cognitive tasks that are perceived as more complex in spite of intact ability.